"Bonafide Tribals": Religion and Recognition among Denizens of Mumbai’s Forest Frontier - Elison, William (Journal for the study of religion, nature and culture, 2010)
This essay discusses a predicament confronting semi-urban members of the Warli community, a tribal (adivasi) group whose settlements occupy the wooded northern frontier of the city of Mumbai. Much of this area is administered as a nature reserve, the Sanjay Gandhi National Park, with adjacent sections having been opened to development by business interests, prominent among them the Bollywood film industry. When first an environmental NGO and then the film studios sought to drive the Warlis from their land, Warli NGOs responded in court first by enumerating their presence and then by establishing a connection between those abstract numbers and constructions of tribals already circulating in legal discourse and other privileged channels—ideas, images, and narratives that could frame them as a certain kind of community whose relation to a certain kind of space gave them legitimate rights of occupancy. At stake in these conflicts, I argue, was the problem of recognition. Invisibility, which had so long defined the condition of denizens of the Indian wilderness, was no longer a refuge; once the forest zone had been absorbed within the realm of polity, it became incumbent on the Warlis to claim recognition as fellow subjects in whatever terms were practicable or be consigned to abjection.